2017
DOI: 10.1111/cbdd.12927
|View full text |Cite
|
Sign up to set email alerts
|

Simplified, serine‐rich theta‐defensin analogues as antitumour peptides

Abstract: θ-defensins belong to the family of host defence peptides. They are the only known example of cyclic polypeptides in animal proteomes. This study presents the synthesis of simplified θ-defensin analogues with pairs of cysteine replaced either by alanine, leucine or serine residues. Cytotoxicity tests were performed on human mammary epithelial (HB2) and breast cancer (SKBR3, MDA-MB-231) cell lines to determine whether peptides are selectively targeting cancer cells. The effect of these peptides was also evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…θ-defensin derivatives specifically inhibit the proliferation of breast cancer cells but spare normal breast epidermal cells [ 287 ]. Homozygous deletion of the θ-defensin gene in different cancers activates oncogenic pathways and suppresses immune response pathways [ 288 ], implicating its potential as a prognostic biomarker for immunotherapy.…”
Section: Activity Of Ampsmentioning
confidence: 99%
“…θ-defensin derivatives specifically inhibit the proliferation of breast cancer cells but spare normal breast epidermal cells [ 287 ]. Homozygous deletion of the θ-defensin gene in different cancers activates oncogenic pathways and suppresses immune response pathways [ 288 ], implicating its potential as a prognostic biomarker for immunotherapy.…”
Section: Activity Of Ampsmentioning
confidence: 99%
“…Furthermore, natural defensins appear to exert antiproliferative and proapoptotic effects on cancer cells and to induce cell cycle arrest ( 44 , 47 51 ), which are evidenced by increases in the levels of phosphorylated retinoblastoma protein, suppressed activities of transcriptional and cell cycle cyclin-dependent kinases and their catalytic cyclin partners ( 52 ), and enhanced expression of caspase 7 and 9 and other markers of apoptosis. Interestingly, human beta-defensin-2 (hBD-2) have been shown to also reduce the viability of melanoma cells through the downregulation of BRAF ( 52 ).…”
Section: Major Therapeutically Relevant Classes Of Ampsmentioning
confidence: 99%
“…Two additional facets of human defensins warrant discussion: first, it is notable that they appear to have an impressive level of specificity for tumor cells, yet do not appear to exert palpable cytotoxic or cytostatic effects against normal untransformed cells ( 48 , 50 , 51 , 54 ). It has been shown that defensins induce apoptosis in MCF-7 cells via the intrinsic pathway, enhanced MAPK p38 phosphorylation, as well as increased expression of cytochrome c, Apaf-1, caspase 7 and 9, but did not affect the membrane potential and calcium flow ( 48 ).…”
Section: Major Therapeutically Relevant Classes Of Ampsmentioning
confidence: 99%
See 1 more Smart Citation
“…The story of therapeutic peptides begins with insulin [ 25 ] (manufactured by recombinant DNA technology in E. coli [ 26 ]) and oxytocin (produced by chemical synthesis elaborated by du Vigneaud in 1953 [ 27 ]), which are the most recognizable manufactured peptide hormones. Peptides show potency in treatment of cancer, asthma, neuropathic pain, stroke, diabetes, HIV, heart disease, and wound healing [ 14 , 28 , 29 ]. Some peptides also have immunoregulatory and anti-inflammatory properties, thanks to which they can be used in the treatment of autoimmune diseases [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%